STRATEGI PENGEMBANGAN USAHATANI KARET DI KABUPATEN KUANTAN SINGINGI - Bamba Indalis (UNIVERSITAS LANCANG KUNING, 2021)
Thepotential for rubber in Kuantan Singingi Regency, Riau Province, has a positif impact on foreign exchange, industrial raw materials, soursce, of income and community welfare. There are 2 types of rubber farming systems implemented by rubber farmers in Kuantan Singingi, namely conventional and auctioned. Conventional farmers are farmers who market bokar directly to toke (big traders). The auction system farmers are a group incorporated in the rubber farmers association in Kuantan Singingi Regency. This research aims to study rubber farming in Kuantan Singingi Regency. Analyzing the efficiency of rubber farming in Kuantan Singingi Regency.Formulating a rubber farming development strategy in Kuantan Singingi Regency.The main problem faced by rubber farmers in Kuantan Singingi Regency in conventional farmers is the price is still under the control of the toke with a weight value of 0.287 while the auction system is the main problem faced is the guidance of rubber farmers is still lacking with a weight value of 0.198. Conventional profitability is seen with an R / C ratio of 1.8 and in rubber farmers auction system with an R / C ratio of 2.14, which means that farming is feasible to proceed. AWOT analysis results show that priority factors are in quadrant III, then the strategy focused for the development of conventional rubber farming that is using the ST strategy that is a strategy that uses strength (internal) farming to minimize / overcome challenges (external) so that the relevant strategy to be implemented for the development of conventional rubber farming in Kuantan Singingi District. AWOT analysis results show that the fact r priority on auction system farmers is in quadrant I, then the strategy focused on developing a rubber farming system is to use an SO strategy that is a strategy that uses strength (internal) farming by utilizing existing opportunities (external) so that the relevant strategy can be implemented for the development of a rubber farming system in the auction system in Kuantan Singingi Regency.